Pemanfaatan Fasilitas Kesehatan Tingkat Pertama (FKTP) oleh Peserta BPJS Kesehatan di Kota Denpasar: Utilization of First Level Health Facilities by Social Security Administrator for Health Participants in Denpasar City - Arini, Ketut Novia (Bali Medika Jurnal, 2020)
The objective of this research is to understand the utilization of primary health facilities in Denpasar throughout 2017 in general. The method used in this research was cross-sectional descriptive. This research involved 10 Public Health Centers (hereafter Puskesmas) and 10 Prime Clinics in Denpasar with total sample of 1000 respondents. Data was collected from medical record of patients (secondary data) and was analyzed univariately. The result of this research shows 50.4% of BPJS on Health’s members in Denpasar are male, 29.8% of respondents are in the age range of 26-45 years old, 83.7% hold non-fee recipients (PBI) membership status, as much as 28% of the respondents visit FKTP three times annually on average, and 91.3% patients visit FKTP with acute disease. It is hoped that members of BPJS on Health could actively play their role to increase the preventive effort by implementing healthy lifestyle to prevent any acute of chronic diseases.